St. Vincent and The Grenadines : Request For Disbursement Under The Rapid Credit Facility and Purchase Under The Rapid Financing Instrument. (IMF Staff Country Reports; Country Report ;, 2014)
On December 24, 2013, a tropical trough system impacted St. Vincent and the Grenadines. The heavy rains resulted in severe floods and landslides, with damages and losses estimated to be equivalent to about 15 percent of GDP. With most of the impact falling on infrastructure, including bridges, roads and hydroelectric facilities, emergency relief costs and rehabilitation and reconstruction expenses are opening a balance of payments gap in 2014.